Scanning Probe Microscopy: Functionalization of Scanning Probe Tips with Epitaxial Semiconductor Layers (Small Methods 3/2017). Issue 3 (March 2017) - Giliberti, Valeria; Sakat, Emilie; Bollani, Monica; Altoe, M. Virginia; Melli, Mauro; Weber‐Bargioni, Alexander; Baldassarre, Leonetta; Celebrano, Michele; Frigerio, Jacopo; Isella, Giovanni; Cabrini, Stefano; Ortolani, Michele
Abstract : A novel nanotechnology approach for the functionalization of scanning probe tips with epitaxial semiconductor material is presented by Michele Ortolani and co‐workers in article number 1600033. The epitaxial material is extracted from micropillars by a lift‐out process directly with the scanning probe and then it is shaped into a pyramidal tip. In this demonstration, the optical properties of scanning probes functionalized with epitaxial germanium are demonstrated by two different infrared nano‐optics experiments.